An Extension of the Inequality of John-Nirenberg (Selecciones Matemáticas, 2019)
The objetive of this note is to present an extension of the inequality of John-Nirenberg relative to a characterization of the spaces of bounded mean oscillation (spaces BMO). Another extension of this inequality is mentioned.
Keywords: John-Nirenberg; BMO; Calderón-Zygmund; function fi; characterization